Antibacterial Activity of Copper Nanoparticles Fabricate via Malva Sylvesteris Leaf Extract - Ismail Haji Zebari, Osama; Yaseen Sharaf Zeebaree, Samie; Yaseen Sharaf Zeebaree, Aemn; Ismail Haji Zebari, Hardan; Ridha Abbas, Hadeel (Kurdistan Journal of Applied Research, 2019)
A Green reduction of copper ions Cu2+ has been achieved by one-step process and at room temperature utilizing Malva sylvesteris. The extract of Malva Sylvesteris leaf has been identified using qualitative tests to detect the bioactive compounds such as flavonoids, polyphenols, terpenoids and carbohydrates. Characterization of copper nanoparticles was diagnosed by Ultraviolet–visible spectroscopy that confirms the band characteristic for copper nanoparticles in the range of 200–700 nm and the role of Malva Selvesteris leaf extract biomolecules was confirmed by Fourier transform infrared spectroscopy. The crystal shape of nanoparticles was confirmed by X-ray diffraction (XRD) at average (20.96 nm) and the peaks correspond to the face centered cubic structure of cooper metal. Effective antiseptic activity of copper nanoparticles determined by measurement of inhibition zone showed against representative microorganism of bacteria (Gram-positive: Clostridium Staph.aureus;) and (Gram-negative: Escherichia col; Pseudomonas; Klebsiella